2018
DOI: 10.4269/ajtmh.18-0206
|View full text |Cite
|
Sign up to set email alerts
|

Altered Systemic Adipokine Levels in Pulmonary Tuberculosis and Changes following Treatment

Abstract: Pulmonary tuberculosis (PTB) is associated with modulation of levels of adipokines, specifically adiponectin and leptin, but the effect of standard antituberculosis treatment (ATT) on the systemic levels of adiponectin, resistin, and leptin has not been well explored. To identify the association of adipokines with PTB and their relationship with disease severity and bacterial burden, we measured the levels of adiponectin, resistin, and leptin in PTB individuals and compared them with latent tuberculosis (LTB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Clinical research has demonstrated that pulmonary tuberculosis is characterized by diminished circulating adiponectin and leptin levels, as well as augmented resistin levels [ 8 ]. Serum adiponectin concentrations have been shown to provide protection against asthma in premenopausal women and adolescent girls [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical research has demonstrated that pulmonary tuberculosis is characterized by diminished circulating adiponectin and leptin levels, as well as augmented resistin levels [ 8 ]. Serum adiponectin concentrations have been shown to provide protection against asthma in premenopausal women and adolescent girls [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, adipokines may play a crucial role in pulmonary diseases, particularly in the context of inflammatory disorders, malignancies, and interstitial lung diseases. However, the associations between adipokines and interstitial lung disease (ILD) [ 4 ], asthma [ 5 ], chronic obstructive pulmonary disease (COPD) [ 6 ], lung cancer [ 7 ], tuberculosis [ 8 ], sleep apnea syndrome (SAS) [ 9 ], and pneumonia [ 10 ] remain unclear. Causality cannot be deduced from the existing evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetics are 1.5 to 3 times more likely to develop active TB [ 63 , 64 ]. Conversely, a meta-analysis by Menon et al [ 65 ] showed that up to 50% of people diagnosed with TB had hyperglycemia at baseline, which remained unresolved in over 10% of cases even after 6 months of effective anti-TB treatment. Although the pathophysiologic basis of hyperglycemia/DM in TB has not been fully elucidated, a role has been postulated for adipokine-mediated alterations in the microenvironment, resulting in increased susceptibility to hyperglycemia through the release of counterregulatory stress hormones (e.g., glucagon, cortisol and growth hormone) [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α completely blocks SREBP-1 expression and its activation ( Sewter et al., 2002 ; Das and Mukhopadhyay, 2011 ). Resistin also links to inflammation and higher resistin levels were observed in tuberculosis and T2D patients ( Youn et al., 2004 ; Gharibeh et al., 2010 ; Das and Mukhopadhyay, 2011 ; Moideen et al., 2018 ). Resistin activates pro-inflammatory cytokines like IL-12 and TNF-α through the NF-κB-dependent pathway in mouse and human macrophages and is directly correlated to glucose homeostasis ( Asensio et al., 2004 ; Silswal et al., 2005 ).…”
Section: Tb-dm Complications and Dm Susceptibility In Tb Patientsmentioning
confidence: 99%